2022
DOI: 10.1093/ijpp/riac004
|View full text |Cite
|
Sign up to set email alerts
|

Service quality in outpatient teaching hospital pharmacies based on the SERVQUAL model: An assessment in the south of Iran

Abstract: Objectives The present study assessed the quality of services in the outpatient teaching hospital pharmacies affiliated to Shiraz University of Medical Sciences, Iran, in 2019 according to the SERVQUAL model to identify areas for improvement. Methods The research was cross-sectional, descriptive and analytical. Patients referred to the outpatient teaching hospital pharmacies affiliated to Shiraz University of Medical Sciences… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…It has been suggested that researchers should modify the existing indicators or develop their own indicators to their socio-demographic, cultural and geographical context based on the SERVQUAL model [16]. Previous studies have measured service quality on the basis of the SERVQUAL model in public hospital [18], hospice care [19], outpatient teaching hospital pharmacies [20], and dental service [21].…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that researchers should modify the existing indicators or develop their own indicators to their socio-demographic, cultural and geographical context based on the SERVQUAL model [16]. Previous studies have measured service quality on the basis of the SERVQUAL model in public hospital [18], hospice care [19], outpatient teaching hospital pharmacies [20], and dental service [21].…”
Section: Introductionmentioning
confidence: 99%